Jed's world : a science fiction novel - Danek, Larry ([Publisher not identified], 2020)
The ability to create living creatures had been easy but to have those beings use initiative and understand complex matters had not been as simple. The only was to get the newly-made ones to progress was to use an existing soul who had already developed the skills or forethought and concept. Success would come in the form of an elderly earth man who was no longer interested in life.George Martin expected to join his wife in the hereafter but as luck would have it, he was given the chance to start over in a new world.